T2‐low severe asthma clinical spectrum and impact: The Greek PHOLLOW cross‐sectional study - Konstantinos Porpodis; Nikolaos Zias; Konstantinos Kostikas; Argyris Tzouvelekis; Michael Makris; George N. Konstantinou; Eleftherios Zervas; Stelios Loukides; Paschalis Steiropoulos; Konstantinos Katsoulis; Anastasios Palamidas; Aikaterini Syrigou; et al. (Clinical and Translational Allergy)
Abstract Background Data on type 2 (T2)‐low severe asthma (SA) frequency is scarce, resulting in an undefined unmet therapeutic need in this patient population. Our objective was to assess the frequency and characterize the profile and burden of T2‐low SA in Greece. Methods PHOLLOW was a cross‐sectional study of adult SA patients. Based on a novel proposed classification system, patients were classified as T2‐low if blood eosinophil count (BEC; cells/μL) was <150, fractional exhaled nitric oxide (FeNO) < 25 ppb and any allergy status or BEC < 150/FeNO < 50 ppb/no allergy or BEC < 300/FeNO < 25 ppb/no allergy. For patients receiving biologics and/or oral corticosteroids, only those with BEC < 150/FeNO < 25 ppb/no allergy/no response to therapy were classified as T2‐low. Secondary outcome measures were: Asthma Control Test (ACTTM), Mini‐Asthma Quality of Life Questionnaire (Mini‐AQLQ), hospital anxiety and depression scale (HADS), and Work Productivity and Activity Impairment:Respiratory Symptoms (WPAI:RS) questionnaire. Results From 22‐Mar‐2022 to 15‐Mar‐2023, 602 eligible SA patients were enrolled. The frequency of T2‐low asthma was 20.1%. Of those, 71.1% had experienced ≥1 clinically significant exacerbations in the past year, 62.8% had ACT score <20 (uncontrolled asthma), and 22.3% were biologic‐treated. Mini‐AQLQ score was <6 (impairment) in 79.5% of patients, HADS‐total score was ≥15 (clinically significant emotional distress) in 43.8%, while median percent activity impairment and work productivity loss were 30.0 for both domains. Clinical and patient‐reported outcomes were worse among patients with ACT‐defined uncontrolled asthma. Conclusions One‐fifth of SA patients present with a T2‐low endotype. These patients frequently have uncontrolled disease and experience impairments in their quality of life, emotions and work ability.